Patos Barcino (Anas flavirostris), Capuchino (Anas versicolor), y Overo (Anas sibilatrix) en el sur del océano Atlántico - Seco Pon, Juan Pablo; Bastida, Julián (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.